EVALUASI CUSTOMER PT POS INDONESIA DITINJAU DARI KEPUASAN KEPERCAYAAN DAN SWITCHING BARRIERS - Edwin Japarianto (Jurnal Manajemen Pemasaran, 2014)
This research is aimed to analyze the evaluation of perceived quality and perceived value to PT. Pos Indonesia customers satisfaction and to examine the customers satisfaction based on trust, customers loyalty and switching barriers. Research data are collected through survey method with interview method straight to 400 respondents who use PT. Pos Indonesia. The technique of collecting sample is using Non probablity sampling. Methodology that is used are CHAID, Suharjo, Split, Penalty-Rewards. Based on several tolls we can collcect almost evaluation result about PT. Pos Indonesia performance.